(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper deals with the accordance's comparison of resources and results of several commercial and solid mechanics numerical modelling software. One of the most common fracture mechanics example is Compact Tension Specimen (CTS) which is used in this paper for testing and comparing the results of commercial solid mechanics numerical modelling software (for instance SolidWorks module CosmosWorks, Unigraphics NX technical analysis module, etc.) using nontrivial examinations to their possibility margins. Standard Griffith (A.A.Griffith) model of energy balance is used in linear models which explores the mesh size influence to the precision of results. Achieved results have been compared mutually and with the examples found in the literature.